Capsaicin Enhances the Drug Sensitivity of Cholangiocarcinoma through the Inhibition of Chemotherapeutic-Induced Autophagy. - Zai-Fa Hong (PLoS ONE, 2015)
Cholangiocarcinoma (CCA), a devastating cancer with a poor prognosis, is resistant to the currently available chemotherapeutic agents. Capsaicin, the major pungent ingredient found in hot red chili peppers of the genus Capsicum, suppresses the growth of several malignant cell lines. Our aims were to investigate the role and mechanism of capsaicin with respect to the sensitivity of CCA cells to chemotherapeutic agents. The effect of capsaicin on CCA tumor sensitivity to 5-fluorouracil (5-FU) was assessed in vitro in CCA cells and in vivo in a xenograft model. The drug sensitivity of QBC939 to 5-FU was significantly enhanced by capsaicin compared with either agent alone. In addition, the combination of capsaicin with 5-FU was synergistic, with a combination index (CI) < 1, and the combined treatment also suppressed tumor growth in the CCA xenograft to a greater extent than 5-FU alone. Further investigation revealed that the autophagy induced by 5-FU was inhibited by capsaicin. Moreover, the decrease in AKT and S6 phosphorylation induced by 5-FU was effectively reversed by capsaicin, indicating that capsaicin inhibits 5-FU-induced autophagy by activating the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway in CCA cells. Taken together, these results demonstrate that capsaicin may be a useful adjunct therapy to improve chemosensitivity in CCA. This effect likely occurs via PI3K/AKT/mTOR pathway activation, suggesting a promising strategy for the development of combination drugs for CCA.